Autotrophic denitrification in constructed wetlands: Achievements and challenges - Ma, Yuhui; Zheng, Xiangyong; Fang, Yunqing; Xu, Kaiqin; He, Shengbing; Zhao, Min (Bioresource Technology, 2020)
[Display omitted] •The current researches in integrating autotrophic denitrification into CWs is reviewed.•Autotrophic denitrification process dependent on electron donor is discussed.•Development and challenges of autotrophic denitrification in CWs is discussed.•Extensive research is required to facilitate autotrophic denitrification in CWs. The use of constructed wetlands for wastewater treatment is rapidly increasing worldwide due to their advantages of low operating and maintenance costs. Denitrification in constructed wetlands is dependent on the presence of organic carbon sources, and the shortage of organic carbon is the primary hurdle for nitrate removal. Therefore, the use of inorganic electronic donors has emerged as an alternative. This paper provides a comprehensive review of nitrate removal pathways using various inorganic electron donors and the performance and development of autotrophic denitrification in constructed wetlands. The main environmental parameters and operating conditions for nitrate removal in wetlands are discussed, and the challenges currently faced in the application of enhanced autotrophic denitrification wetlands are emphasized. Overall, this review illustrates the need for a deep understanding of the complex interrelationships among environmental and operational parameters and wetland substrates for improving the wastewater treatment performance of constructed wetlands.